A Cross-Sectional Study of Coronavirus Disease Prevention Practices among University Staff and Students in Durban, South Africa in 2020-2021 - Maureen Nokuthula Sibiya; Kelechi Elizabeth Oladimeji; Felix Emeka Anyiam; Olanrewaju Oladimeji (MDPI AG, 2023)
Background: Globally, the COVID-19 pandemic has had a negative impact on individuals, education, and the economy. During its peak, the pandemic forced school closures. Although there is currently no cure for corona virus, non-pharmaceutical measures can help prevent its spread. Among these preventive measures are regular handwashing with soap and water or the use of hand sanitizers, avoiding touching the mouth, nose, and eyes, social distancing, and the use of face masks. As a result, this study investigated COVID-19 prevention practices among Durban University of Technology staff and students in South Africa. Methods: Using a cross-sectional study design, data were gathered online via self-administered, structured questionnaires from 5849 university students and staff members between May 2020 and March 2021. Utilizing descriptive statistics, the characteristics of the study sample were reported. Using logistic regression models, the relationship between demographic characteristics and the overall level of COVID-19 preventive practices was evaluated. Results: The multivariate logistic regression model showed statistically significantly associations for COVID-19 preventive practices by: male (AOR: 9.815, 95% CI: 1.721-55.959, p = 0.01) compared to female participants, single participants (AOR: 6.012, 95% CI: 2.070-17.461, p = 0.001) compared to other marital categories, and those in the faculty of Health Sciences (AOR: 1.721, 95% CI: 1.023-2.894, p = 0.041) compared to other faculties. Conclusions: Overall, the study's preventive practices were commendable; they were also influenced by socio-demographic factors such as age, gender, marital status, and university faculty. Increasing age was associated with reduced compliance with COVID-19 preventive practices. In addition, men demonstrated greater caution than women.